1975
DOI: 10.1111/j.1471-4159.1975.tb03679.x
|View full text |Cite
|
Sign up to set email alerts
|

GABA CONTENT AND GLUTAMIC ACID DECARBOXYLASE ACTIVITY IN BRAIN OF HUNTINGTON'S CHOREA PATIENTS AND CONTROL SUBJECTS1

Abstract: —GABA contents are significantly decreased in the caudate nucleus, putamen‐globus pallidus, substantia nigra, and occipital cortex in autopsied brain from Huntington's chorea patients, as compared to values in the same regions from control subjects who have died without neurological disease. Homocarnosine levels are lower in choreic than in control brain, but only in the putamen‐globus pallidus and the cerebellar cortex are the differences significant. Activity of the enzyme which synthesizes GABA, glutamic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

1977
1977
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(18 citation statements)
references
References 14 publications
3
14
1
Order By: Relevance
“…With regard to the effect of postmortem delay in an unfrozen state, we found no significant influence (Table 2). Previous studies on mouse and monkey brains have, however, shown a slow decline over a period of 24-120 hours (Urquhart et al, 1975;Sherif et al, 1991). Furthermore, our present results on the stability of rat brain GABA-T activity indicated that there is a loss of approximately 20% of the activity immediately after death (Table 4).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…With regard to the effect of postmortem delay in an unfrozen state, we found no significant influence (Table 2). Previous studies on mouse and monkey brains have, however, shown a slow decline over a period of 24-120 hours (Urquhart et al, 1975;Sherif et al, 1991). Furthermore, our present results on the stability of rat brain GABA-T activity indicated that there is a loss of approximately 20% of the activity immediately after death (Table 4).…”
Section: Discussioncontrasting
confidence: 52%
“…Urquhart, 1975;Fariello and Ticku, 1983;Fibiger and Lloyd, 1984;Gale, 1989;Perry etal., 1989; see also Lloyd and Morselli, 1987 for a review). Roberts (1972) suggested that, in schizophrenia, there might be a deficiency in the activity of certain neurons that utilize GABA as an inhibitory neurotransmitter and this hypothesis of an imbalance between dopaminergic and GABA-ergic neuronal activity in schizophrenia was further developed by van Kammen (1977).…”
Section: Introductionmentioning
confidence: 97%
“…Postmortem studies have indicated a loss of choline acetyltransferase (CAT) activity presumably associated with atrophy of cholinergic interneurons in the striatum, and a reduction in glutamic acid decarboxylase (GAD) (Bird and Iversen, 1974;Bird et al, 1973;McGeer and McGeer, 1976;Urquart et aL, 1975). These results together with the observation that dopamine antagonists improve the choreiform movements (Klausaus and Rubovits, 1972) suggest the presence of dopaminergic overactivity due to the loss of cholinergic and gabergic inhibition.…”
Section: Discussionmentioning
confidence: 87%
“…2 Alterations in gaba-ergic pathways and GABA levels have been associated with several neurological disorders. [3][4][5][6][7] Accordingly, the in vivo assay of GABA has been a goal of much work on changes in neurotransmission in subjects, e.g. after pharmacological treatment.…”
Section: Introductionmentioning
confidence: 99%